Changes in the malignant female reproductive system tumors disease spectrum at the Beijing obstetrics and gynecology hospital in the past 60 years - He, Yue; Wang, Sheng-Qian; Ji, Chen; Liu, Zhen-You; Wei, Jia-Hui; Wang, Ming; Wu, Yu-Mei; Wang, Yan; Xu, Xiao-Hong (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate the epidemiological trends in the incidence, age distribution, and pathological types of malignant female reproductive system tumors over the past 60 years at the Beijing Obstetrics and Gynecology Hospital.MethodsThe types of diseases and basic clinical information of 18,921 patients with malignant female reproductive system tumors admitted to our hospital between January 1960 and December 2019 were collected.ResultsA total of 18,921 patients were diagnosed and treated in the last 60 years. Since the establishment of the Department of Gynecological Oncology at our hospital in 1970, the number of patients with gynecological tumors has doubled, and the number of tumor types has also increased, with the highest incidence of cervical cancer, followed by endometrial cancer, ovarian cancer, and trophoblastic tumors. The three most common tumor types were most prevalent among women aged over 36 years. The average age of patients was 49.43 ± 11.65 years for those with cervical cancer, 53.95 ± 9.45 years for endometrial cancer, and 43.04 ± 13.79 years for ovarian cancer. Over the last 20 years, the age of patients with cervical cancer has been decreasing, and the age of patients with endometrial or ovarian cancers has slowly increased. Squamous cell carcinoma (85.61%–100%) was the most prevalent cervical cancer subtype; while, adenocarcinoma (88%–100%) was the most common endometrial cancer subtype and epithelial carcinoma was the most common ovarian cancer subtype.ConclusionThe establishment of a gynecological oncology subspecialty correlated with improved diagnostic capabilities and a marked increase in the number of cases. The observed epidemiological shifts underscore the need for targeted screening programs, as well as preventive and control policies. Furthermore, the proportion, classification, and age distribution characteristics of malignant tumors in the female reproductive system changed over time. These findings provide a foundation for refining national cancer prevention policies.